The acquisition of the voicing contrast in Thai: A study of voice onset time in word-initial stop consonants - Jack Gandour (2018)
This paper reports on a cross-sectional acoustical investigation of the development of the voicing contrast in Thai word-initial stops. Voice onset time (VOT) productions associated with three bilabial stops (/b p p h /), three alveolar stops (/d t t h /), and two velar stops (/k k h /) were measured in seven 3-year-old children, seven 5-year-old children, seven 7-year-old children, and seven adults. Within each age group, differences in mean VOT between homorganic stop consonants indicated that 3-year-olds have acquired all voicing contrasts except /b/ vs. /p/ and /d/ vs. /t/. By age five, children have acquired all voicing contrasts. However, as measured by differences in mean VOT across age groups, 5-year-olds still do not produce /b/ or/d/ in an adult-like manner. Issues concerning the order of acquisition and nature of development of stop consonants are discussed. © 1986, Cambridge University Press. All rights reserved.